PERBANDINGAN PEMERIKSAAN JUMLAH TROMBOSIT METODE MANUAL (AMONIUM OKSALAT) DAN METODE PENCITRAAN DIGITAL (IMAGEJ) PADA KAMAR HITUNG IMPROVED NEUBAUER - Riki Gusmana; Mohamad Firman Solihat; Betty Nurhayati; Adang Durachim; Erick Kristian (Jurnal Kesehatan Siliwangi, 2025)
ABSTRACT Platelet count examination is a crucial parameter in evaluating hemostatic function, especially in diagnosing diseases such as dengue fever. This study compares the manual method using Ammonium Oxalate reagent with the digital imaging method utilizing ImageJ software on the Improved Neubauer chamber. The research aims to evaluate the differences between these methods and compare them with the automated method (Hematology Analyzer) as the gold standard. The study employed an observational analytic design with a cross-sectional approach. Samples consisted of blood from patients undergoing complete hematology examinations at RSUD Bedas Kertasari, Bandung Regency. Results from the three methods were compared to determine accuracy, efficiency, and objectivity. The results of the study showed the quantitative distribution of platelet counts using automatic (Hematology Analyzer), manual (Ammonium oxalate) and digital imaging (ImageJ) tools obtained the average values ​​respectively: 302,400 cells/mm3, 297,500 cells/mm3, 305,000 cells/mm3. There was no statistically significant difference in the test of platelet count examination data pairs between the automatic method (Hematology Analyzer) and the manual method (Ammonium oxalate) and between the automatic method data pairs (Hematology Analyzer) and the digital imaging method (ImageJ). While in the test of platelet count examination data pairs in the Improved Neubauer counting chamber between the manual method (Ammonium oxalate) and the digital imaging method (ImageJ) there was a statistically significant difference, but clinically the difference was still within the permissible threshold.